How does the Internet enhance the subjective well-being of elderly individuals in China? - Dong, Xuebing; Meng, Shunjie; Chen, Danbo (Frontiers in Psychology, 2022)
Although several studies have explored the relationship between the Internet and elderly individuals, little is known about whether and how the Internet affects elderly individuals’ subjective well-being (SWB) from multiple perspectives. This study examines the effects of the Internet on physical satisfaction and life satisfaction and explores the potential mechanisms by which the Internet produces its effects on elderly individuals. Using nationally representative data from the China General Social Survey (CGSS), this study finds that the Internet has a significant positive impact on physical satisfaction and life satisfaction of the elderly in China. The mechanism analysis shows that the Internet can improve the level of health insurance participation, which we interpret as potential mechanisms through which the Internet positively affects physical satisfaction among elderly individuals. Correspondingly, the Internet affects life satisfaction of elderly individuals by influencing social networks. Further heterogeneity tests find that the effect is stronger for urban areas, male and high human capital samples. This study highlights the important micro effects of the Internet and provides a reference for exploring the mechanism of the Internet affecting SWB.